أسلوب الإيجاز بالحذف عند الشيخ الشعراوي رحمه الله من خلال تفسيره - بن عيشة, عائشة; بورزمة, الزهرة (University of Eloued-جامعة الوادي, 2022)
"الحمد لله رب العالمين، وبعد: يدرس هذا البحث أسلوب من الأساليب البلاغية في القرآن الكريم من خلال تفسير الشيخ الشعراوي، وهو "" أسلوب الإيجاز بالحذف في القرآن الكريم من خلال تفسير الإمام الشعراوي ــ رحمه الله ـــ "". ويدور حول إشكالية مفادها كيف استفاد الإمام الشعراوي من خلال درايته الواسعة بالبلاغة في الكشف عن وجوه البيان من خلال أسلوب الإيجاز في القرآن الكريم ؟ وما هي أبرز الأغراض التي تكلم عليها، وأثرها في تفسيره ؟ وقد تمت معالجة إشكالية هذا البحث في ثلاثة مباحث: الأول بعنوان: ترجمة الإمام الشعراوي والتعريف بتفسيره، والثاني: التعريف بأسلوب الإيجاز، والثالث: تطبيقات حول أسلوب الإيجاز بالحذف في تفسير الشعراوي، حيث أن الشعراوي بين أغراض وأنواع إيجاز الحذف. ومن أهم النتائج التي خلصنا إليها في هذا البحث هي: أبدع الإمام الشعراوي رحمه الله في الكشف عن كثير من صور بلاغة أسلوب الإيجاز في القرآن الكريم من حيث حذف الحرف أو الكلمة أو الجملة، إذ وقف عند جملة من المعاني الدقيقة التي تكشف لنا وجه إعجاز هذا الكتاب العزيز في عرضه لدلالاته ومعانيه.""This research studies one of the rhetorical methods in the Noble Qur’an through the interpretation of Imam Shaarawy، which is “the method of brevity by deletion through the interpretation of Shaarawy ”. How did Imam Shaarawy benefit from his knowledge of rhetoric in devising the method of abbreviating deletion from the Holy Qur’an? What are the most prominent purposes that he spoke about and that had an impact on his interpretation? Several questions fall under this form: What is meant by brief? What is its most important purpose? What is its importance in understanding the Holy Quran? And where lies in the statement of meaning? Where the problem of this research was dealt with in three sections: the first is entitled: Imam Shaarawy’s translation and definition of his interpretation، the second: the definition of the method of brevity، and the third: applications about the method of brevity by deletion in the interpretation of Shaarawy، as Shaarawy is between the purposes and types of brevity of omission. Among the most important results that we reached in this research are: -Imam Muhammad Metwally Al-Shaarawi is one of the greatest scholars، as he was a scholar، thinker، writer and politician. -The method of brevity is one of the rhetorical arts in the science of semantics.
م\كرة ماستر
Keywords: الإيجاز بالحذف، الشيخ الشعراوي، تفسير الشعراوي; Abbreviation by omission, Chikh Chaaraoui, Explanation of Chaaraoui